Factors affecting the change in the poverty index of households in Phonxay District, Luang Prabang Province - HER, bounthai; SIPHANTHONG, Bounthavy; SIOUDOMPHAN, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Factors affecting the change in the poverty index of households in Phonxay District, LuangPrabang Province, is a study in the form of a survey using a questionnaire as a tool to collect data from a sample group to study the elements of poverty indicators and factors affecting the change in the poverty index of households in Phonxay District, LuangPrabang Province. The results of the study found that the poverty of households in Phonxay, LuangPrabang province, is caused by the number of members and dependents who are children, the elderly, and the disabled in many households. Household members are mainly engaged in farming and gardening, resulting in each household having an average income household/year and an average income person/year that is relatively low: 20,418,118 kip and 3,708,861 kip, respectively, which still cannot meet the conditions and standards of all. At the same time, there are some people who are still in debt due to borrowing for agricultural production and for use during illness. There is only one way to travel in and out, which is road transportation, but the access road to the residence is difficult and can only be used in certain seasons, and there is no access road to the production site. Most people still do not have access to the electricity grid and water supply systems. Many households still do not have permanent houses, only semi-permanent houses and temporary houses. In addition, people's communication is based on the use of landline phones, making it impossible to access information with full efficiency. For the results of the study on the factors affecting the change in the household poverty index of the people of Phonxay District, LuangPrabang Province, it was found that: the number of members in the household and the income factor of the household have a relationship in the same direction with the poverty index of the people of Phonxay District with a confidence level of 95%; The factor of the number of members who can generate income in the family has a relationship in the opposite direction with the poverty index of the people in Phonxay city of LuangPrabang province, and the factor of access to a high level of education among the household members has a relationship in the opposite direction with the poverty index of the people in Phonxay city of LuangPrabang province with a confidence level of 90%.